A massive systematic infection of Encephalitozoon cuniculi genotype III in mice does not cause clinical signs - Sak, Bohumil; Brdíčková, Klára; Holubová, Nikola; Květoňová, Dana; Hlásková, Lenka; Kváč, Martin (Microbes and infection, 2020)
Encephalitozoon cuniculi genotype III disseminated intensively into most of the organs in all strains of mice, followed by a chronic infection with massive microsporidia persistence in immunodeficient mice and a partial decrease in C57Bl/6 mice. Treatment with 0.2 mg Albendazole/mouse/day temporarily reduces the number of affected organs in immunocompetent C57Bl/6 mice, but not in CD4-/- and CD8-/- mice. The application of medication temporarily decreased the spore burden at least by one order of magnitude in all groups. These results demonstrate that the E. cuniculi genotype III infection had a progressive course and surprisingly, Albendazole treatment had only a minimal effect. The E. cuniculi genotype III spore burden in individual organs reached up to 108 or 109 in immunocompetent or immunodeficient mice, respectively; however, these mice did not demonstrate any obvious clinical signs of microsporidiosis, and the immunodeficient mice survived longer. Our findings clearly show that the survival of mice does not correspond to spore burden, which provides new insight into latent microsporidiosis from an epidemiological point of view.
Keywords: Chlorocebus aethiops; CD4 Antigens; Vero Cells; antigeny CD4; CD8(−/−) mice; C57Bl/6 mice; Vero buňky; Albendazole; encephalitozoonóza; Genotype; zvířata; myši; myši inbrední C57BL; Mice; Cercopithecus aethiops; Encephalitozoonosis; CD4(−/−) mice; albendazol; antigeny CD8; Mice, Inbred C57BL; Encephalitozoon cuniculi genotype III; Encephalitozoon cuniculi; genotyp; Animals; CD8 Antigens; Disease Models, Animal; modely nemocí na zvířatech